Expanding Access to Naloxone: A Necessary Step to Curb the Opioid Epidemic. (29th September 2023) - Houser, Ryan
Abstract: The COVID-19 Pandemic has exacerbated the already worsening opioid epidemic within the United States. With a continuing increase in opioid overdose deaths, measures are needed to halt the needless number of deaths and begin on a path of recovery to address all the factors that impact the epidemic. The CDC has provided various recommendations to combat the increases in opioid overdose deaths. These recommendations have included expanded distribution and use of naloxone and overdose prevention education as essential services for people most at risk of overdose. While strategies should include the increase in community resources for those with opioid disorder and shifting the perspectives of healthcare to view opioid disorder as a chronic illness that can be treated with medication such as buprenorphine, these methods are not immediate enough to stop the trend in deaths. The United States must take immediate action to expand access to and use of Naloxone for the public and first responders. Naloxone alone cannot address the magnitude of this epidemic, but it is an essential first step in preventing immediate death while a multimodal strategy is enacted to fully protect those most at risk.